Biophysical studies of selected intrinsically disordered proteins: insect stress-response peptides and cancer-linked variants of human p53 transactivation domain - Goss Schrag, Lynn (Kansas State University, 2020)
The intrinsically disordered proteins (IDPs) or regions (IDRs), which do not have a single well-defined structure, participate in critical roles of signal transduction in Eukaryotic cells. Using humans as an example, more than 1/3rd of all protein sequences contain an identifiable >30 residue stretch that can be defined as intrinsically disordered. Interestingly, this intrinsic structural flexibility often facilitates binding promiscuity of IDP or IDR and renders them ideal for participating in complex cell signaling interaction networks by acting either as a hub, an integrator of cell signaling, or as a ligand, an inducer of one or more pathways through receptors. Though modern biophysical approaches are optimized for well-folded proteins and segments but the understanding of the structural dynamics as it relates to critical aspects of biological activities for most IDPs is still relatively poor. In this dissertation, we will explore two distinct IDP structure activity relationship and discuss biophysical studies on two systems: The results of our first study involve the novel cytokine-like stress-response peptides of the insect Manduca sexta which contains highly dynamic termini that are critical for its activity. The second study, the transactivation domain of critical eukaryotic transcription factor and tumor suppressor p53 that acts as a critical integrator of intracellular signaling in regulating cell-fate. In both cases, studies carried out with selective mutagenesis reveal small changes in the preferred dynamics of the IDPs for each system that correspond to pronounced differences in physiological outcomes.
Keywords: Nuclear magnetic resonance spectroscopy; Intrinsically disordered proteins; Stress-response peptides; Cytokines; P53; Cancer